Portfolio as controlling and structuring mediation of professional knowledge - Buysse, Alexandre A.J.; Vanhulle, Sabine (Swiss Journal of Educational Research, 2010)
According to our Vygotskian perspective, a portfolio is a tool that mediates not only the extent to which the students control their own learning, but also a mediation of the procedures linked to knowledge. We consider portfolio as both a controlling and a structuring mediation. We examine how it could enable first to see, and then to internalise, the creation process of professional knowledge based on referential and experiential knowledge at the disposal of the student. Following a short definition of the portfolio, the mediations are described as well as the peculiar points about professional knowledge. To illustrate our findings we describe two different sets of intervention-portfolio developed in the context of our teacher training institutions.